2010
DOI: 10.1002/ceat.201000024
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Indirect Wollastonite Carbonation Route for CO2 Sequestration

Abstract: A new CO 2 sequestration approach through indirect wollastonite carbonation is proposed to mitigate anthropogenic CO 2 emissions from fossil fuel combustion. The wollastonite carbonation process includes three steps: (1) dissolution of wollastonite in hydrochloric acid to leach Ca 2+ from mineral matrix; (2) reaction of the resulting CaCl 2 solution with CO 2 in triisooctylamine (TIOA) at low temperature, producing CaCO 3 and an amino acid complex; (3) regeneration of the extractant and acid by backextraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…There are a variety of indirect methods being studied, most of which involve varying the pH of the solution [187,188]. Generally, indirect carbonation involves a minimum of two steps: extraction of the Ca or Mg reactive components, and reaction with carbon dioxide to form carbonates.…”
Section: Indirect Carbonationmentioning
confidence: 99%
“…There are a variety of indirect methods being studied, most of which involve varying the pH of the solution [187,188]. Generally, indirect carbonation involves a minimum of two steps: extraction of the Ca or Mg reactive components, and reaction with carbon dioxide to form carbonates.…”
Section: Indirect Carbonationmentioning
confidence: 99%
“…Several studies have been made to study mineral reactivity, energy balance, intense grinding in presence of gaseous CO 2 and dynamics of CO 2 in pores [20]. Rock-Eval analysis [21] to quantify carbonation yields has revealed that a highly reactive system will rapidly obstruct and limit pore space volume in an ultramafic formation with important consequences in terms of reactivity and injectivity.…”
Section: Co 2 Fixation By Stimulated Weatheringmentioning
confidence: 99%
“…To test efficacy of artificial weathering, pilot experiments are being carried out to study mineral reactivity, energy balance, type of CO 2 injection and dynamics of CO 2 in pores. Naturally occurring silicate materials like forsterite, wollastonite and synthetic magnesium silicates have been studied by intense grinding in presence of gaseous CO 2 (Zhana et al, 2010). In a biomimetic process (Liu et al, 2005) enzyme carbonic anhydrase as catalyst was used to accelerate the rate of precipitation of mineral carbonate with industrial wastewater as cation source.…”
Section: Stimulated Weathering Of Mineral Rocksmentioning
confidence: 99%